The Influence of Learning Motivation on Learning Outcomes with Family Environment as a Moderating Variable - Zainal, Abidin; Yoyok, Soesatyo; Lucky, Rachmawaty (Technium Social Sciences Journal, 2025)
This study aims to analyze the influence of learning motivation on learning outcomes with family environment as a moderating variable. The population in this study were eighth-grade students of SMP Negeri 31 Samarinda in the academic year 2023/2024 in Samarinda City, East Kalimantan Province, Indonesia. The sampling technique used was Proportional Random Sampling, which resulted in 117 students. The analysis used in this study was Structural Equation Modeling (SEM) with SmartPLS 4.0. The results of this study indicate that learning motivation has a positive and significant effect on learning outcomes. However, the interaction between family environment and learning motivation does not have a significant effect on learning outcomes. Therefore, support and an active role of the family in creating a conducive learning environment at home are very important to maximize the positive influence of learning motivation on student learning outcomes.